Effects of pH, competing ions and aging on arsenic(V) sorption and isotopic exchange in contaminated soils. (June 2019) - Rahman, M.S.; Clark, M.W.; Yee, L.H.; Comarmond, M.J.; Payne, T.E.; Burton, E.D.
Abstract: Cattle tick control in Australia using arsenicals from early 1900s to 1955 has led to the existence of some 1600 contaminated sites in northern New South Wales alone. Sorption processes play key roles in controlling arsenic (As) accessibility and subsequent mobility in these dip soils. As(V) sorption and accessibility in three As-contaminated soils and two uncontaminated soil types (ferralitic and sandy soils) are investigated utilizing batch sorption experiments and isotopic exchange techniques. The aged contaminated soils displayed little or no ability to sorb additional As(V), and increasing the soil pH caused a substantial reduction in As(V)-sorption and resulting in As(V)-release. Isotope exchange experiments further supported that any further exposure of the aged-contaminated-soils to additional As(V) increased As-mobilization potential. Amendments of phosphate greatly decreased As(V) sorption in aged-contaminated-soils where As-sorption sites were more highly saturated, whereas phosphate had little effect on As(V) sorption in pristine soils. Similarly, sulfate reduced As(V) sorption, but these effects were less marked than those for phosphate, hence, the application of both PO4 3− and SO4 2− in As(V)-contaminated-soils may lead to potential As(V)- mobilization. Conversely, Ca 2+ increases As(V)-sorption, which is consistent with expected changes in the surface charge characteristics from Ca 2+ sorption, and/or Ca-AsO4 precipitations, consequently Ca 2+ amendments may improve As-retention, thereby decreasing As accessibility from cattle dip soils. Therefore, the detailed knowledge presented here provides new insights that may be useful for the assessment and management of the As-contaminated soils. Graphical abstract: Image 1 Highlights: An increase in pH in aged contaminated soils release potential As. A potential As mobilization for application of PO4 3− & SO4 2− in contaminated soils. Amendment of soils with Ca 2+ increase As retention capacity. Addition of As to aged contaminated soils lead to an increased As mobilization.